2001
DOI: 10.1002/bit.1108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anaerobic culture acclimation on the degradation kinetics of various substrates

Abstract: The adaptation of an anaerobic culture (anaerobic sludge) to a specific substrate brings significant changes to its microbial population. These changes can be described by the sludge's ability to treat various substrates such as carbohydrates or proteins or "intermediate" products of anaerobic metabolism such as L-lactic, propionic, and acetic acids. The activity of the sludge with respect to a specific substrate is a critical parameter, because the anaerobic degradability of wastewaters depends strongly on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 19 publications
0
9
0
3
Order By: Relevance
“…It was previously reported that carbohydrates could suppress the synthesis of exopeptidases, a group of enzymes facilitating protein hydrolysis [29]. Anaerobic degradation of proteins and the effects of ammonia on this mechanism were recently investigated in detail [30][31][32][33][34][35]. Casein is the major protein in milk composition and in dairy effluents.…”
Section: General Characteristics Of Dairy Wastewatersmentioning
confidence: 99%
“…It was previously reported that carbohydrates could suppress the synthesis of exopeptidases, a group of enzymes facilitating protein hydrolysis [29]. Anaerobic degradation of proteins and the effects of ammonia on this mechanism were recently investigated in detail [30][31][32][33][34][35]. Casein is the major protein in milk composition and in dairy effluents.…”
Section: General Characteristics Of Dairy Wastewatersmentioning
confidence: 99%
“…The GAMS modeling language was used to formulate the optimization problem. The leastsquares objective was to select the best kinetic parameter values so as to minimize the squared residuals between the experimentally measured and the respective predicted concentrations (Gavala and Lyberatos, 2001).…”
Section: Kinetic Expressions and Computational Methodsmentioning
confidence: 99%
“…Upon such effects, the culture may transform into a new one. Adapting anaerobic mixed culture on lignocellulosic substrates at low temperature may come at the expenses of fats-and protein-metabolizing microorganisms (Gavala and Lyberatos 2001;Gavala et al 1999;Guieysse et al 2001). Precisely, adaptation may induce a population shift from the substrate sensitive to the substrate tolerant microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the kinetics of the culture may change as well. Gavala and Lyberatos (2001) reported that adaptation affected the consumption and kinetics (the maximum specific utilization rate) of various compounds in the mixed anaerobic culture significantly. The adaptation affects the stoichiometry of the reactions which produce the volatile fatty acids during the acidogenesis and acetogenesis (Gavala and Lyberatos 2001).…”
Section: Introductionmentioning
confidence: 99%